Enhanced electrochemical performance of zinc/bromine redox flow battery with carbon-nanostructured felt generated by cobalt ions. (15th August 2022) - Naresh, Raghu pandiyan; Surendran, Ammu; Ragupathy, Pitchai; Dixon, Ditty
Abstract: Surface properties of graphite fibers greatly determine the performance of flow batteries. In this work, graphite felt is modified with transition metal ion (cobalt)-assisted thermal treatment process. This multi-step thermal treatment process generated well aligned carbon nanostructures as well as large amount of oxygen functional groups on graphite fiber surface. Such an electrode surface architecture is highly beneficial for the performance of Zinc-Bromine redox flow batteries, as it facilitates superior charge as well as mass transfer, associated with dense organic polybromide phase formed during charging. Consequently, the flow cell with modified felt, decorated with carbon nanostructures, operates at higher energy efficiency (84%) compared to pristine felt (68%) and conventionally thermally treated felt (68%). Postmortem analysis using scanning electron microscopy reveals the durability of carbon nanostructure on the felt, as these structures are observed to remain intact after long-term cycling (100 cycles) experiments. Graphical abstract: Unlabelled Image Highlights: Graphite felt with uniform carbon nanostructure generated by Co ions assisted thermal treatment method. Nanostructure architecture facilitated the mass transfer of dense polybromide phase into the electrode. Flow cell with nanostructure felt exhibited higher energy efficiency (84 %) than pristine felt (68 %). Nanostructure felt showed stable long cycling performance with 80 % energy efficiency.